Proceedings of the 31st European Conference on Cognitive Ergonomics 2019
DOI: 10.1145/3335082.3335125
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for the Development of a Dynamic Adaptive Intelligent User Interface to Enhance the User Experience

Abstract: The aim of this paper is to present PhD research that aims to enhance the User Experience by proposing a framework that combines the three core components of: dynamic interfaces; adaptive interfaces; and intelligent interfaces. Initial research into the field has identified a gap at the intersection of these types of interaction. A dynamic interaction understands the user, their device and their physical environment to provide a basic User Experience. An adaptive interaction understands the user's capabilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Johnston et al [10] identified the standardised process for the creation of IUIs as an under-researched area. The work aims to improve user experience universally through provision of a framework for the development of IUIs.…”
Section: Related Workmentioning
confidence: 99%
“…Johnston et al [10] identified the standardised process for the creation of IUIs as an under-researched area. The work aims to improve user experience universally through provision of a framework for the development of IUIs.…”
Section: Related Workmentioning
confidence: 99%
“…greater focus, reduced distraction and attenuated anxiety). These appear in Figure 1 and include dynamic, adaptive and intelligent interfacesof which-research has identified an intersectional gap in their interactivity (Johnston et al, 2019). Specifically, dynamic systems understand the user, their device and their environment to provision a basic user experience.…”
Section: Figure 1: Engineering Components Of Adaptive Systemsmentioning
confidence: 99%
“…While many contemporary CNNs learn hierarchical descriptors from input stimuli and then describe input data into smaller, highly abstract representations, SensorAble-like those studies from Barros, Johnston et al, (2017;2019)-does not use a strict classification technique. Rather than learning tiered contours and shapes used in general image recognition tasks, convolutional units instead train on sensorial and spatial information sometimes originally existing as images and other times transformed into visual data (Speck et al, 2016).…”
Section: Figure 3: Combined Multi-sensory Inputs (Across Three Domains) May Provide Greater Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…The third related research paradigm named dynamic taxonomies, prunes the taxonomy according to the informal keyword given manually by the user, e.g. in [15,24,29,31,50,56,58]. Using dynamic taxonomies, the user can most directly interact with the online portal, but the domain is semantically reduced according to the keyword.…”
Section: Introductionmentioning
confidence: 99%